The The Influence of Mind Mapping Model towardsthe Result on Economical Lesson for Tenth Grade Islamic Senior High School in MAN 2 Kutai Kartanegara - Hairani Alfi Ananda; Nikie Raidatulfaridah Mulyono; Nanang Rijono; Sudarman Sudarman; Achmad Ruslan Afendi (EduLine: Journal of Education and Learning Innovation, 2023)
The study examines the use of mind mapping model and its result in Economical lesson for tenth grade Islamic Senior High School in MAN 2 Kutai Kartanegara that involves two classes consisting of 35 male and 43 female students. This study uses experimental research by using post-test only control group design as the method. The data collection technique is used by using documentation, interview with the teacher who teaches Economical lesson, test, and questionnaire of the students’ respond. The technique of analyzing the data by using t-test to examine the hypothesis. The results of the study show that the implementation of using mind mapping as a leaning model is running well. The student from experimental class, X-IPS 1 or social studies class 1shows the significant changes and conventional class, X-IPS 2 social studies class 2 shows not really the significant changes. But, from these two classes together show development from how they study, their interests in learning Economical lesson, they become active, creative, and critical student especially their result in score to pass the standard lesson value in Economic is 75 in their school. Based on the research, the average score of the first post-test shows 98,5 in experimental class and 87,64 in conventional class. In the second post-test, the averagescore in experimental class having more significant difference until 10,86. Then, the average score for both two post-test in experimental class is 86,91 and conventional class is 82,07. From ten questions of questionnaire are reached each questions get 70% for the statement of agreement in using mind mapping as learning model to understand and learn Economical lesson. The analyzed of the data by using t-test shows tcount equals 5,931 and ttable equals 5%, and the percent of the freedom (dk) equals 76 or 1,991. Because tcount is bigger than ttable, means the use of mind mapping to increase the result of the students’ learning for economical lesson is accepted and revealed. The use of using mind mapping is also expected to solve the lower student speed in learning a certain lesson, the student to learn other lessons to increase their understanding, and the student and teacher are able to have good interaction and bounding to prepare them in facing the real word especially that links with Economy.